Elucidating the protective mechanisms of umbilical cord mesenchymal stem cells against stenosis-induced deep venous thrombosis during pregnancy: a transcriptomic and metabolomic study - Zhang, Junrong; Sun, Feng; Yao, Jingjing; Zhang, Jianlin; Wu, Xirong; Xu, Yunzhao; Zhang, Yuquan; Cheng, Xi (Frontiers in Cell and Developmental Biology, 2026)
ObjectiveThis study aims to integrate metabolomics and transcriptomics data to investigate the protective effects of umbilical cord mesenchymal stem cells (UC-MSCs) on obstetric deep vein thrombosis (DVT) and to elucidate the underlying molecular mechanisms.MethodsA pregnant rat model of DVT was established using the inferior vena cava (IVC) stenosis method. The protective effects of UC-MSCs on DVT and endothelial cell injury were evaluated both in vivo and in vitro. Transcriptomic and metabolomic analyses were performed to identify differentially expressed genes (DEGs) and differentially abundant metabolites (DMs) in IVC tissues from DVT rats and those treated with UC-MSCs. Correlation analysis was conducted to associate relevant metabolites and RNAs. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis was applied to DEGs and DMs to identify significantly involved pathways. The mRNA–transcription factor regulatory network was constructed using Cytoscape software. Receiver operating characteristic (ROC) curves for immune regulatory genes and DEGs were generated with the R package pROC. The mMCP-counter algorithm was used to assess the distribution and abundance of immune cell subsets.ResultsThe rat DVT model was established using the IVC stenosis method. Administration of UC-MSCs reduced thrombus burden, promoted angiogenesis, and mitigated hydrogen peroxide-induced endothelial injury in the DVT model. Integrated transcriptomic and metabolomic analyses revealed significant correlations between four key metabolites—pyridine, nicotinamide, L-phenylalanine, and L-leucine—and 24 interacting genes. These metabolites served as critical nodes within the regulatory network. KEGG enrichment analysis indicated that pathways such as amino acid biosynthesis and phenylalanine metabolism are implicated in the therapeutic effects of UC-MSCs on pregnancy-related DVT. Notably, the hub gene Got2 was associated with amino acid biosynthesis, while both Got2 and Maoa were involved in phenylalanine metabolism. Furthermore, seven immune-regulatory genes, including Gaa and Tlr2, demonstrated significant classification performance (area under the curve [AUC] > 0.8) in ROC curve analysis.ConclusionThis study elucidates the protective mechanisms of UC-MSCs in the treatment of DVT in pregnant rats induced by the inferior vena cava stenosis model. These findings provide a scientific basis for the further evaluation and development of UC-MSCs-based therapeutic strategies for DVT during pregnancy.